Improving student’s learning result using e-encyclopedia of plants structure and function in Senior High School - Komaria, Siti; Ningsih, Kurnia; Titin, Titin (CAHAYA PENDIDIKAN, 2023)
This research aims to see improvements in the learning result of students using E-Encyclopedia of Plant Structure and Function as a learning material. This is a Class Action Research that was conducted in 4 stages consist planning stages, action stages, observation stages, reflection stages and was carried out in 3 learning cycles. The research was conducted at SMP Negeri 18 Pontianak. The research’s population was student of 8th grade and the research’s sample is 15 students of 8th grade in A class. The students learning results in cycle I were averaged 85.3 with an 80% satisfaction percentage; in cycle II it was 86.7 with a 100% satisfaction percentage; and in cycle III it was 87.6 with a 100% satisfaction percentage. There is an increase in the average value of each cycle so that in line with the results obtained, it can be concluded that E-Encyclopedia in teaching and learning process on Plant Structure and Function can improve the learning result of the students.